An Exploration of Learning Motivation and Reading Comprehension of Accounting Students Using Quizizz - Widyasari, Mustika Dyah; Wijirahayu, Suciana (Universitas Muhammadiyah Gresik, 2025)
Abstract This exploration study explores the role of Quizizz in improving learning motivation and reading comprehension among Accounting students at state a vocational high school (SMKN 21 Jakarta) in the 2024 school year. Using a survey-based methodology, this study investigates how this gamified learning platform affects students' engagement and their ability to comprehend English reading content. A structured survey was used to gather information from 36 accounting students about their Quizizz experiences, opinions and difficulties. The results showed mixed results; some students felt that this platform improved their motivation and comprehension, while others expressed doubts about its efficacy. This study emphasizes the ability of digital platforms such as Quizizz to create an interactive and engaging learning environment, while overcoming barriers in students' adaptation to new technologies. The findings provide useful insights for educators and augment the ongoing discussion about incorporating technology into education,offering practical implications for classroom practices as well as recommendations for further research and wider implementation. Keywords: Quizizz; Learning Motivation; Reading Comprehension.